The Steady Development of Digital Law: New Challenges of Artificial Intelligence - ALSAMARA , Tareck; GHAZI , Farouk (Journal of Ecohumanism, 2024)
The article addresses the issue of the steady development of digital law in the face of artificial intelligence (AI) technology. Some international institutions are focusing on the potentially dangerous aspects of artificial intelligence. In March 2024, the first legal text from the European Union relating to artificial intelligence was issued. The rules of digital law pertaining to artificial intelligence are spread across all branches of law, and both international and national laws contribute to the continuous development of this field. The article uses a deductive approach by showing how international law and national law have contributed to the development of digital laws to accommodate artificial intelligence technology. The article concludes that such laws have effects on other branches of law, and can help to find solutions to the problems of using artificial intelligence. Similarly, we seek to find solutions to problems in other areas such as civil and commercial law. Such laws as the Personal Data Protection Law, the rules of the Consumer Protection Law, and the Copyright Protection Law that apply to digital content play an important role in preventing abuses. Such protections are also needed in the field of AI.